Gritty Peers - Effrosyni Adamopoulou; Yaming Cao; Ezgi Kaya (Institute of Labor Economics (IZA), 2024)
We use the National Longitudinal Study of Adolescent to Adult Health to explore how high school peers' grit, a personality trait characterized by perseverance and passion, influences long-term outcomes. Exploiting random variation within schools across cohorts, we find that peer grit significantly increases future earnings, especially for students from disadvantaged backgrounds. We identify two key mechanisms: an increased likelihood of employment in jobs aligned with career goals and a reduced probability of feeling overwhelmed by difficulties. Additionally, peer grit leads to higher job satisfaction and asset accumulation. Thus, peer grit's effects extend beyond short-term educational performance and persist into adulthood.
Keywords: I24; J13; J24; 330; grit; peer effects; long-term outcomes; Add Health